A novel HPLC method for the simultaneous determination of empagliflozin and dapagliflozin: Development, validation, robustness testing and greenness assessment - Kladi, Eleftheria; Zerva, Maria; Dotsikas, Yannis (Archives of Pharmacy, 2024)
Empagliflozin (EMPA) and Dapagliflozin (DAPA) are mainly recommended for the treatment of type 2 diabetes mellitus and heart failure. Based on the principles of green analytical chemistry, a simple, rapid and robust HPLC method was developed for the determination of both analytes in bulk. An isocratic protocol was developed using a C18 column, with a mobile phase consisting of just 30% organic modifier (ACN), while the remaining 70% was HPLC water. The run was completed within 4 min, with a flow rate of 1.20 mL/min, while UV detection took place at 230 nm. The method was then validated according to the ICH Q2 (R1) guidelines, and all the parameters examined were within the specified limits. Furthermore, the robustness of the method was evaluated by employing a factorial experimental design. Finally, the environmental friendliness of the proposed method was assessed by using the Analytical GREEness (AGREE) metric tool. The proposed method can be used for analysis of EMPA and DAPA in bulk, with potential application to the relevant pharmaceuticals.
Keywords: empagliflozin; dapagliflozin; AGREE tool; robustness testing; validation